Accelerator brake safety control device and vehicle applying same - JIN YANDONG (2015)
The invention discloses an accelerator brake safety control device and a vehicle applying the device. The accelerator brake safety control device comprises a brake rod, a brake pedal, an accelerator rod and an accelerator pedal, and is provided with a clutch device, wherein the clutch device is provided with a transmission device; the transmission device is connected with the accelerator rod or the accelerator pedal through an accelerator connecting device; the clutch device is mounted on a bracket; and the other end of the bracket is connected with the brake rod or the brake pedal through a brake connecting device. An accelerator and a brake of the control device can be separately controlled; and the oil reducing brake can be performed even if the accelerator is wrongly stepped in an emergency situation.